Clinical use of pasireotide for Cushing's disease in adults - Ceccato F; Scaroni C; Boscaro M (Dove Medical Press, 2015)
Filippo Ceccato, Carla Scaroni, Marco Boscaro Endocrinology Unit, Department of Medicine, Padova University Hospital, Padova, Italy Cushing’s disease: Excessive corticotroph hormone levels sustained by an adrenocorticotropic hormone-secreting pituitary adenoma lead to a severe clinical condition caused by excess cortisol secretion, called Cushing’s disease (CD). Neurosurgery and radiotherapy are used to treat the pituitary adenoma directly, but new medical treatments targeting the corticotroph cells have recently become available. Pasireotide: This is a novel multireceptor ligand somatostatin (SST) analog with a high binding affinity for SST receptor 5, the predominant receptor in human corticotroph adenomas that is not downregulated by high cortisol levels (as SST receptor 2 is). Pasireotide has been recently approved by the European Medical Agency and the US Food and Drug Administration for treating adults with CD with recurrent hypercortisolism after surgery, or for whom surgery is not an option. A dose of 600–1,200 µg twice a day can normalize urinary free cortisol levels after 3 months of treatment in up to 28% of patients, reducing their blood pressure and improving their weight, lipid profile, and quality of life. Combining pasireotide with cabergoline to achieve a greater hormone response can normalize cortisol secretion in 50% of patients, and adding ketoconazole induces biochemical control in most patients with CD. Safety and hyperglycemia: The adverse effects of pasireotide are similar to those of other SST analogs, including diarrhea, nausea, and biliary sludge or gallstones. Hyperglycemia is common during pasireotide treatment, which affects the secretion of pancreatic insulin and intestinal glucagon-like peptide 1. Self-monitoring is essential to achieve good metabolic control, and endocrinologists should first administer metformin if insulin resistance is evident and then add dipeptidyl peptidase 4 inhibitors/glucagon-like peptide 1 receptor agonists or insulin. Conclusion: In recent years, medical treatment with pasireotide has been proposed as monotherapy for adults with CD characterized by mild to moderate hypercortisolemia, as well as in combination with other available therapies. It is generally well-tolerated, but endocrinologists need to monitor glucose levels to ensure prompt treatment. Keywords: Cushing’s disease, pasireotide, medical therapy, hyperglycemia, safety